Cocaine Cowboys: Visualizing Aging Masculinities in Galician Narco Noir - Barbour, Catherine (Taylor & Francis, 2024)
Arguably the most recognizable figure of Galician manhood on screen today is the aging drug kingpin, as the burgeoning cinematic genre of Galician narco noir exposes global audiences to Galicia’s key role as a gateway for the steady flow of cocaine into Europe. This article engages with current debates in aging, masculinities and disability studies to examine the depiction of the elderly male drug lords in two recent works pertaining to the Galician narco noir genre; Nemo Bandeira, protagonist of the series Vivir sin permiso (2018-2020), based on a short story by Manuel Rivas, and Antonio Padín from the film Quien a hierro mata (2019), a Galician-Spanish co-production directed by Paco Plaza. It is argued that the intersection of aging masculinities with illness and disability in the representation of older drug lords perpetuates but also renegotiates preconceptions about Galician manhood, reflecting broader issues relating to the representation and commodification of gender, age, illness, disability, and power in popular culture. In the context of the stereotypically “masculine” sphere of organised crime, analysis of how the older male demographic is represented in noir brings insight into the construction of Galician identities on screen more generally, signalling to perceptions of the wider societal impact of crime, corruption, and impunity in Galician society.
PUBLISHED
Special Issue: Aging Men and Masculinities in Contemporary Spanish Cinema and Audiovisual Industries ed. by Raquel Medina and Josep María Armengol
Keywords: Ageing; Identities in Transformation; Galician audiovisual culture; noir